Transcription factor Nrf1 is topologically repartitioned across membranes to enable target gene transactivation through its acidic glucose-responsive domains. - Yiguo Zhang (PLoS ONE, 2014)
The membrane-bound Nrf1 transcription factor regulates critical homeostatic and developmental genes. The conserved N-terminal homology box 1 (NHB1) sequence in Nrf1 targets the cap'n'collar (CNC) basic basic-region leucine zipper (bZIP) factor to the endoplasmic reticulum (ER), but it is unknown how its activity is controlled topologically within membranes. Herein, we report a hitherto unknown mechanism by which the transactivation activity of Nrf1 is controlled through its membrane-topology. Thus after Nrf1 is anchored within ER membranes, its acidic transactivation domains (TADs), including the Asn/Ser/Thr-rich (NST) glycodomain situated between acidic domain 1 (AD1) and AD2, are transiently translocated into the lumen of the ER, where NST is glycosylated in the presence of glucose to yield an inactive 120-kDa Nrf1 glycoprotein. Subsequently, portions of the TADs partially repartition across membranes into the cyto/nucleoplasmic compartments, whereupon an active 95-kDa form of Nrf1 accumulates, a process that is more obvious in glucose-deprived cells and may involve deglycosylation. The repartitioning of Nrf1 out of membranes is monitored within this protein by its acidic-hydrophobic amphipathic glucose-responsive domains, particularly the Neh5L subdomain within AD1. Therefore, the membrane-topological organization of Nrf1 dictates its post-translational modifications (i.e. glycosylation, the putative deglycosylation and selective proteolysis), which together control its ability to transactivate target genes.